2022
DOI: 10.1186/s13052-022-01306-6
|View full text |Cite
|
Sign up to set email alerts
|

Significance of biomarkers in stewardship program in pediatric patients infected with Aspergillus species

Abstract: Background The potential use of biomarkers in the diagnosis of fungal infections is a challenge. The aim of this study was to evaluate the role of a biomarker-guided antifungal stewardship program for hospitalized pediatrics suffering from invasive aspergillosis (IA). Methods Pediatric patients with suspected probable or proven IA were enrolled in this study. Demographic data were collected from their records. Clinical samples were examined by wet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Unfortunately, there are limited data in the literature about the role of the PCT level as a diagnostic marker for IA. The cut-off value for PCT > 260 pg/mL with a sensitivity of 80.8% and specificity of 100% was reported in pediatric patients suffering from IA [ 27 ]. In Robinson et al, after 3 days, a PCT level > 500 pg/mL occurred in 81% (17/21) of the patients with invasive fungal diseases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, there are limited data in the literature about the role of the PCT level as a diagnostic marker for IA. The cut-off value for PCT > 260 pg/mL with a sensitivity of 80.8% and specificity of 100% was reported in pediatric patients suffering from IA [ 27 ]. In Robinson et al, after 3 days, a PCT level > 500 pg/mL occurred in 81% (17/21) of the patients with invasive fungal diseases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Buckland et al reported circulating sTREM-1 levels in experimental fungal asthma peaked on day 30 in the mice model [ 35 ]. The cut off value for sTREM1 > 190 pg/mL with sensitivity 71.2%, specificity 100%, PPV 100% and NPPV 46.2% was reported in infected pediatric patients with Aspergillus species [ 27 ]. In the literature, we could not find a study that included the cut-off value of sTREM-1 in patients suffering from IA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations